2001
DOI: 10.1002/1522-2675(20011219)84:12<3796::aid-hlca3796>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerization of Phenols, Part III, The Anthrone−Anthrol Equilibrium in Aqueous Solution

Abstract: Dedicated to Prof. A. Jerry Kresge on the occasion of his 75th birthdayThe equilibrium between 10H-anthr-9-one and 9-anthrol favors the ketone, which ionizes as a carbon acid in aqueous base. Rates of equilibration were measured over the pH range 1 ± 13 in aqueous solution (258, ionic strength I 0. m). Five independent thermodynamic and kinetic parameters were determined by analysis of the pH-rate profile: the equilibrium constant of enolization, pK E 2.17, the ionization quotient of anthrol, pQ E a 7.84, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…Differences in bond length are rarely greater than Table 1 Gas phase absolute electronic energy in atomic units (hartrees), and relative energies (kcal mol À1 ) for tropolone (species (1) and (2)) and 3,5-and 3,6-cycloheptadiene-1,2-dione (molecules (3) and (4), respectively), evaluated at HF and B3LYP levels of theory, with 6-311++G ** and aug-cc-pVDZ basis sets, as well as with the G3 method Table 2 Absolute and relative electronic energy in atomic units and kcal mol À1 , respectively, at HF and B3LYP levels of theory for the four molecules in aqueous solution using the Onsager dipole and polarizable continuum solvent reaction field models in combination with 6-311++G ** and augcc-pVDZ basis sets 0.02 Å while bond angles, for the most part, agreed to within a degree. The largest difference between aqueous and gas phase bond angles was found for: A (3,4,5) in (1) with value +3.3°, A (12,14,15) in (2) is À0.9°, A (2,13,11) in (3) is +1.2°, and A (5,7,9) in (4) is +1.5°. The B3LYP gas phase optimized geometry of tropolone agrees very well with previous B3LYP/6-31+G * [15] and MP2/6-31G ** [14] calculations.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Differences in bond length are rarely greater than Table 1 Gas phase absolute electronic energy in atomic units (hartrees), and relative energies (kcal mol À1 ) for tropolone (species (1) and (2)) and 3,5-and 3,6-cycloheptadiene-1,2-dione (molecules (3) and (4), respectively), evaluated at HF and B3LYP levels of theory, with 6-311++G ** and aug-cc-pVDZ basis sets, as well as with the G3 method Table 2 Absolute and relative electronic energy in atomic units and kcal mol À1 , respectively, at HF and B3LYP levels of theory for the four molecules in aqueous solution using the Onsager dipole and polarizable continuum solvent reaction field models in combination with 6-311++G ** and augcc-pVDZ basis sets 0.02 Å while bond angles, for the most part, agreed to within a degree. The largest difference between aqueous and gas phase bond angles was found for: A (3,4,5) in (1) with value +3.3°, A (12,14,15) in (2) is À0.9°, A (2,13,11) in (3) is +1.2°, and A (5,7,9) in (4) is +1.5°. The B3LYP gas phase optimized geometry of tropolone agrees very well with previous B3LYP/6-31+G * [15] and MP2/6-31G ** [14] calculations.…”
Section: Resultssupporting
confidence: 89%
“…In a number of chemical systems, however, this trend is not followed. Examples of recently studied [1][2][3][4][5][6][7][8] molecules in which the enol structure is observed to predominate include hydroxycyclopropenone [8] and phenol [6,7]. Ab initio calculations of the tautomeric equilibrium constant on the latter are found to be in excellent agreement with experiment, and confirm the exclusive presence of phenol, while high-level computations on the former species in both gas and aqueous solution phase predict that equilibrium is directed toward the enol rather than to 1,2-cyclopropanedione.…”
Section: Introductionsupporting
confidence: 94%
“…Figure 1A shows optical absorption spectra of 9-anthrone/9-anthranol in tetrachloroethylene (TCE, non-interacting solvent), DEA and TEA (electron donating solvents). Freiermuth et al [5] reported that 9-anthrone/9-anthranol exist in different tautomeric forms, namely like 9-anthrone (ANT) in TCE and acetonitrile, but 9-anthranol (ANTH) in aliphatic amine solvents, such as DEA and TEA, whereas both tautomers are present in alcoholic solvents. The presence of ANTH form in amine solvents is clearly confirmed by the appearance of a new band in 330 -450 nm region of the optical Figure 2B).…”
Section: Introductionsupporting
confidence: 52%
“…The tautomerization enthalpy of 9-anthrol and 9-anthrone Although tautomerization reaction (4) is not isodesmic, we may nonetheless compare its enthalpy values, which are found from taking the difference of our quantum chemically calculated enthalpies of formation of the two isomers, and from experiment and associated analysis [16].…”
Section: Anthronementioning
confidence: 99%